Thermo-chemical compatibility of hafnium diboride with yttrium aluminum garnet at 1500 °C in air. Issue 9 (September 2015) - Winder, S.L.; Ruggles-Wrenn, M.B.; Parthasarathy, T.; Key, T.; Carney, C.M.
Abstract: Due to its high thermal conductivity and oxidation resistance at very high temperatures, hafnium diboride (HfB2 ) is being considered for use as a leading edge material on sharp-bodied reentry vehicles. In structural applications, HfB2 is likely to operate at elevated temperature in proximity to other refractory materials. The thermo-chemical compatibility of HfB2 with (1) single-crystal Y3 Al5 O12 (SX YAG) and (2) Al2 O3 (alumina) was examined in multiple contact combinations during furnace heat treatment exposures at 1500 °C in air. The reaction products were characterized using optical microscopy, SEM, EDS, and XRD. The results are presented and possible mechanisms are discussed.